Penggunaan Lagu “I See the Light” untuk Memperkaya Kosakata Bahasa Inggris di MTS Terpadu Berkah Palangka Raya dalam Program Pengabdian Masyarakat - Siti Anisah; Hesty Widiastuty; Misda Amallia Tuah Aji (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
The purpose of this community service activity is to enhance the English vocabulary mastery of students in class IX.A at MTs Terpadu Berkah Palangka Raya through the implementation of the "I See the Light" song-based learning method. The learning process was carried out in three stages: first, students listened to the song without the translation; second, students listened to the same song with lyrics and translation; and third, students participated in a vocabulary quiz to assess their understanding of the new vocabulary they had learned. Observations during the activity showed that students were more actively engaged and enthusiastic in the learning process and discussions. Based on these findings, it can be concluded that using songs as a learning medium has a positive impact on improving students' English vocabulary mastery in a fun and interactive way. However, there were some challenges related to the unclear volume of the song and the instability of the power supply. Therefore, the recommendation for future research is to ensure clear audio and stable power supply to support the effective implementation of the activities.